Differential Impact of Pay Satisfaction Dimensions on Job Performance and Turnover Intentions in Pay for Performance Systems: The Mediating Role of Affective Commitment - Javad, Shahina; R.K, Premarajan (Asian Journal of Empirical Research, 2018)
The purpose of the present study was threefold. First, to test the validity of the dimensions of pay satisfaction in pay for performance systems. Second, to study the relative effects of different pay satisfaction dimensions on individual work outcomes. Third, to examine potential mediating role of affective commitment in the pay satisfaction-individual work outcome relationship. A two- sample cross-sectional survey conducted among sales executives and sales managers of two different organizations offer support for the distinctiveness of four pay satisfaction dimensions viz., fixed pay level, variable pay level, pay structure and administration, and variable pay procedure satisfaction. The findings of path analyses indicated that the dimensions differentially predicted the outcome variables. The results reported that affective commitment was not a significant mediator between pay satisfaction dimensions and work outcomes, except between variable pay level satisfaction and job performance in the first sample. However, affective commitment was significantly related to turnover intentions. Implications for theory and practice are discussed.